2019
DOI: 10.18203/2320-6012.ijrms20194977
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and skills towards e-learning in first year medical students

Abstract: Background: With digitization the e-learning modalities are being increasingly used by medical students. These often help the first MBBS students to overcome limitations of conventional teaching methods like didactic lectures. However, e-learning is not official part of medical education in India and the awareness about its use among medical students need to be evaluated. Aim and objective of the study was to assess the extent to which MBBS first year students use e-resources for learning as well as to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
(23 reference statements)
3
8
0
Order By: Relevance
“…However, there are many issues with online education and e-learning that need to be addressed. 16 The findings of current study were not unexpected. These are in line with the study done by Chaudhuri et al, 1 who found positive correlation between depression and stress scores with r = 0.765; depression and anxiety scores with r = 0.63 and stress and anxiety scores with r = 0.73.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, there are many issues with online education and e-learning that need to be addressed. 16 The findings of current study were not unexpected. These are in line with the study done by Chaudhuri et al, 1 who found positive correlation between depression and stress scores with r = 0.765; depression and anxiety scores with r = 0.63 and stress and anxiety scores with r = 0.73.…”
Section: Discussionsupporting
confidence: 55%
“…15 This pre-validated questionnaire has seven items for each of the three scales designed to measure the negative emotional states of depression anxiety and stress. The questions 3,5,10,13,16,17, and 21 form the depression scale; questions 2, 4, 7, 9, 15, 19, and 20 forms the anxiety scale while questions 1, 6, 8, 11, 12, 14, and 18 are covered in stress scale. A four-point severity/ frequency scale was used to rate the extent to which the respondents had experienced each symptom over the past week from "never" (0) to "most of the time" (3).…”
Section: Methodsmentioning
confidence: 99%
“…11 In India, up to 84% of first-year medical students recommended conventional teaching to be supplemented with e-learning. 12 Whereas e-learning has been assimilated in most institutions in the developed world, academic institutions in low-and middle-income countries (LMICs) have not fully scaled up e-learning. 13 Challenges of e-learning in medical education in these countries include inadequate resources in terms of infrastructure (gadgets and internet) and skilled professionals to implement this platform.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In India, up to 84% of first-year medical students recommended conventional teaching to be supplemented with e-learning. 12 …”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] There is opinion that conventional teaching should be supplemented with computer and web-based e-learning. [ 4 ] Studies suggest that e-learning should be further utilized in a blended learning environment to support face-to-face teaching and allow for flexibility in delivery of medical education. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%